2015
DOI: 10.1017/s0950268815002149
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of diagnostic tests for adenovirus,Bordetella pertussisand influenza virus infections in German adults with longer lasting coughs

Abstract: Laboratory tests in adult outpatients with longer lasting coughs to identify a potential causal pathogen are rarely performed, and there is no gold standard for these diagnostic tests. While the diagnostic validity of serological tests for pertussis is well established their potential contribution for diagnosing adenovirus and influenza virus A and B infections is unclear. A sentinel study into the population-based incidence of longer lasting coughs in adults was done in Rostock (former East Germany) and Krefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In this study, the actual sensitivity and specificity of the viral culture, as determined by Bayesian LCM statistical analysis, was 72.2% and 90.8% respectively, although they are traditionally considered to be 100%. Our analysis is comparable to that of Sobotzki et al, who applied LCM to analyze the true sensitivity of a combined set of tests for pertussis, adenovirus, and influenza A and B in a large population of adult patients with respiratory disease and cough and reported that LCM is a welldocumented and statistically valid tool in the absence of a gold standard test [12].…”
Section: Accuracy Of Viral Culturesupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, the actual sensitivity and specificity of the viral culture, as determined by Bayesian LCM statistical analysis, was 72.2% and 90.8% respectively, although they are traditionally considered to be 100%. Our analysis is comparable to that of Sobotzki et al, who applied LCM to analyze the true sensitivity of a combined set of tests for pertussis, adenovirus, and influenza A and B in a large population of adult patients with respiratory disease and cough and reported that LCM is a welldocumented and statistically valid tool in the absence of a gold standard test [12].…”
Section: Accuracy Of Viral Culturesupporting
confidence: 77%
“…The absolute accuracy of each diagnostic test was evaluated using Bayesian LCMs [12,15]. In brief, Bayesian LCMs assess the accuracies of various diagnostic tests based on the actual disease status.…”
Section: Statistical Analysis -Bayesian Latent Class Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA has been used extensively in the social sciences but is now increasingly used to examine diagnostic tests in medicine. 11 It uses the observed patterns of test results to calculate the prevalence of the underlying condition, which otherwise cannot be directly observed, as well as the sensitivity and specificity of the tests. We used LCA to understand the three available tests for LTBI among a cohort of persons at high risk for LTBI.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic serology is relevant for pertussis and mycoplasma infections [13,26], and in 9 patients with IgM antibodies to M. pneumoniae, we assumed a polyclonal response to multiple other antigens. Although viral serology is sometimes regarded as obsolete, we have recently shown that applying latent class analysis for validating diagnostic methods in the absence of a Bgold standard,^single-sample viral serology may identify additional cases [27].…”
Section: Discussionmentioning
confidence: 99%